Monte Carlo simulation of growth of porous SiOx by vapor deposition. - Burlakov, V; Briggs, G; Sutton, A; Tsukahara, Y (2001)
A random network model containing defects has been developed and applied to the deposition of amorphous SiOx films on a flat substrate. A new Monte Carlo procedure enables dangling bonds to migrate and annihilate. The degree of porosity in the films is found to increase with oxygen content. As the oxygen content increases a larger fraction of pore surfaces is covered with oxygen, and the density of dangling bonds on pore surfaces decreases. Oxygen plays the role of a surfactant, lowering the energies of pore surfaces and enhancing the porosity of amorphous SiO2 compared to amorphous Si.